(untitled) (Global Conference on Medical and Health Sciences, 2026)
Background: Wearable sensor technology combined with artificial intelligence enables continuous physiological monitoring of children in ambulatory settings, extending clinical surveillance beyond hospital environments. Objective: To comprehensively review wearable AI applications in pediatric health monitoring, evaluate clinical performance, and identify priorities for future development and regulatory pathways. Methods: Systematic review of 74 studies and 12 regulatory submissions covering pediatric wearable AI applications in cardiology, neurology, endocrinology, and general health monitoring. Results: Pediatric-specific wearable AI demonstrated clinical-grade performance for cardiac rhythm monitoring (AUC-ROC 0.94), seizure detection (sensitivity 87.3%), continuous glucose monitoring (MARD 8.2%), and respiratory rate monitoring (mean absolute error 1.8 breaths/minute). Eighteen pediatric wearable AI devices have received FDA clearance or CE marking since 2022. Conclusion: Wearable AI monitoring technologies are approaching clinical-grade performance across multiple pediatric health domains, with accelerating regulatory approval and deployment in specialty pediatric care.